THE UTILISATION OF FACEBOOK GROUP IN BUILDING SOCIAL MEDIA-BASED BRAND COMMUNITY BY A SMALL MEDIUM ENTERPRISE IN YOGYAKARTA - Ambar Sari Dewi (Jurnal Sosiologi Reflektif, 2020)
Internet and social media play important role in fostering both the creation of identities and the development of brand community. Brand community is a community of consumers of a specific brand that are socially constructed and shaped. However, research on this topic are mostly investigated at large enterprises context, leaving some gaps at small-medium enterprises (SMEs) context. SMEs, particularly in developing countries such as Indonesia, hold important role to the country’s economic development. Therefore, this study aims to examine how SMEs build social media-based brand community by using qualitative research as its approach and applied a case study research method to investigate a Yogyakarta-based SME, AB. Findings show that AB build social media-based brand community on Facebook group with the help of its loyal customers. Strong relationship and intense interaction formed between the AB’s owner and some loyal customers are characteristics of social media-based brand community found in this research.